The functions and clinical application potential of exosomes derived from mesenchymal stem cells on wound repair: a review of recent research advances - Qin, Xinchi; He, Jia; Wang, Xiaoxiang; Wang, Jingru; Yang, Ronghua; Chen, Xiaodong (Frontiers in Immunology, 2023)
Wound repair is a complex problem for both clinical practitioners and scientific investigators. Conventional approaches to wound repair have been associated with several limitations, including prolonged treatment duration, high treatment expenses, and significant economic and psychological strain on patients. Consequently, there is a pressing demand for more efficacious and secure treatment modalities to enhance the existing treatment landscapes. In the field of wound repair, cell-free therapy, particularly the use of mesenchymal stem cell-derived exosomes (MSC-Exos), has made notable advancements in recent years. Exosomes, which are small lipid bilayer vesicles discharged by MSCs, harbor bioactive constituents such as proteins, lipids, microRNA (miRNA), and messenger RNA (mRNA). These constituents facilitate material transfer and information exchange between the cells, thereby regulating their biological functions. This article presents a comprehensive survey of the function and mechanisms of MSC-Exos in the context of wound healing, emphasizing their beneficial impact on each phase of the process, including the regulation of the immune response, inhibition of inflammation, promotion of angiogenesis, advancement of cell proliferation and migration, and reduction of scar formation.